Synthetic Gene Drives in Plants: Development Strategies, Potential Applications, and Ethical Considerations - Yawen Liu; Bingke Jiao; Wenfeng Qian (Modern Agriculture)
ABSTRACT We are facing significant agricultural and environmental challenges, including herbicide‐resistant weeds that compromise crop yields and invasive plant species that disrupt local ecosystems. Traditional crop breeding methods are increasingly seen as ineffective in the face of these issues. One innovative approach involves the use of gene drives, a technology that enables targeted genetic modifications to transmit at a super Mendelian rate (>50%) and therefore, rapidly propagate through natural populations. In this perspective, we introduce the principles underlying our development of a plant synthetic toxin‐antidote drive, CAIN (CRISPR‐Assisted Inheritance utilising NPG1). We evaluate the potential of gene drives to alter the genetics of weed populations or suppress invasive plant populations. We explore various factors that influence the effectiveness of gene drives, including the emergence of suppressor mutations and life‐history traits such as sexual and asexual reproduction patterns, seed and pollen dispersal methods, and the variability in plant generation times. Additionally, we discuss the biosafety concerns related to gene drive experiments and field releases, strategies to counteract unwanted gene drives, and the ethical implications, particularly considering the risk of the intentional misuse of gene drive technology and the need for robust regulatory and monitoring frameworks.